Hydrological Risks in Natural Hazards Focused on the Role of the Water: Studies on Landslides - Sousa, Luis (2020)
Landslides are one of the most important natural hazards on Earth. Landslide mechanisms related to hydrology are analyzed with a focus on the major risks, and formal risk assessment methodologies are presented. The management of accidents in slopes is discussed, with particular emphasis on Hong Kong and to Rio de Janeiro. Specific aspects of slope instability in the state of Rio de Janeiro are discussed, with a focus on cases that occurred in the mountainous region of the State. The megadisaster occurred in 2011, with high number of deaths and significant economic losses, is studied with particular incidence in individual landslides. A description of occurrence of large landslides in China is also presented. The modeling of catastrophic flow-type slide at Shenzhen landfill induced by intense rainfall is introduced and referred to large number of landslides happened during the Wenchuan earthquake in 2008 is mentioned.